Disease course of inflammatory bowel disease unclassified in a European population‐based inception cohort: An Epi‐IBD study. Issue 6 (21st January 2019) - Burisch, Johan; Zammit, Stefania Chetcuti; Ellul, Pierre; Turcan, Svetlana; Duricova, Dana; Bortlik, Martin; Andersen, Karina Winther; Andersen, Vibeke; Kaimakliotis, Ioannis P; Fumery, Mathurin; Gower‐Rousseau, Corinne; Girardin, Giulia; et al.
Abstract: Background and Aim: A definitive diagnosis of Crohn's disease (CD) or ulcerative colitis (UC) is not always possible, and a proportion of patients will be diagnosed as inflammatory bowel disease unclassified (IBDU). The aim of the study was to investigate the prognosis of patients initially diagnosed with IBDU and the disease course during the following 5 years. Methods: The Epi‐IBD study is a prospective population‐based cohort of 1289 IBD patients diagnosed in centers across Europe. Clinical data were captured prospectively throughout the follow‐up period. Results: Overall, 476 (37%) patients were initially diagnosed with CD, 701 (54%) with UC, and 112 (9%) with IBDU. During follow‐up, 28 (25%) IBDU patients were changed diagnoses to either UC ( n  = 20, 71%) or CD ( n  = 8, 29%) after a median of 6 months (interquartile range: 4–12), while 84 (7% of the total cohort) remained IBDU. A total of 17 (15%) IBDU patients were hospitalized for their IBD during follow‐up, while 8 (7%) patients underwent surgery. Most surgeries ( n  = 6, 75%) were performed on patients whose diagnosis was later changed to UC; three of these colectomies led to a definitive diagnosis of UC. Most patients ( n  = 107, 96%) received 5‐aminosalicylic acid, while 11 (10%) patients received biologicals, of whom five remained classified as IBDU. Conclusions: In a population‐based inception cohort, 7% of IBD patients were not given a definitive diagnosis of IBD after 5 years of follow‐up. One in four patients with IBDU eventually was classified as CD or UC. Overall, the disease course and medication burden in IBDU patients were mild.